The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.19127/mbsjohs.624390
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workload Perception and Occupational Stress on Medical Error Attitudes of Nurses Working in Surgical Clinics

Abstract: Objectives: The study was conducted to determine workload perception and effects of occupational stress on medical error attitudes of nurses working in surgical clinics. Method: This descriptive study was conducted with 100 nurses employed at surgery clinics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…In this study, no significant difference was found between the approach to medical error average sub-dimension score and sociodemographic characteristics. Similar results were obtained in other studies in the literatüre [11,35]. In another studies [18,36] conducted on nurses a significant difference was found between gender, the clinic they worked in, years of work experience, and approach to medical error sub-dimension.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, no significant difference was found between the approach to medical error average sub-dimension score and sociodemographic characteristics. Similar results were obtained in other studies in the literatüre [11,35]. In another studies [18,36] conducted on nurses a significant difference was found between gender, the clinic they worked in, years of work experience, and approach to medical error sub-dimension.…”
Section: Resultssupporting
confidence: 89%
“…These are the factors that will increase the possibility of error by healthcare professionals. Additionally, the number of patients who are cared for, the number of nurses working, working with inadequate personnel, stress of the work environment, feelings of boredom and burnout are among the causes of medical errors [22,25,35,37].…”
Section: Resultsmentioning
confidence: 99%
“…Although the MEAS has been applied in various settings with nurses, nursing students, and physicians, it has not been used with NLs 13,17-19 . The results of the study provide insights into the views of NLs on medical error perception, approach, and cause.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has focused on the clinical caregiver's (nurses) emotional sequelae following a serious medical error 2,17 . This current study focused on the NLs' views on medical errors and support systems.…”
Section: Discussionmentioning
confidence: 99%